P064 Impact of COVID-19 on physical and mental health of people with inflammatory conditions: the ICEPAC survey. (23rd April 2022) - Hider, Samantha; Muller, Sara; Gray, Lauren; Manning, Fay; Brooks, Mike; Heining, Dominic; Menon, Ajit; Packham, Jonathan; Raghuvanshi, Subhra; Roddy, Edward; Ryan, Sarah; Scott, Ian; et al.
Abstract: Background/Aims: Concerns about the risk of COVID-19 infection led to guidelines advocating shielding for many people with inflammatory conditions. We aimed to assess the impact of the pandemic on the self-reported physical and mental health of people with inflammatory conditions. Methods: 2024 patients with inflammatory conditions (RA, PsA, AS, SLE and other) were randomly selected from electronic health records. Survey invites were sent (August 2021 to coincide with relaxation of COVID restrictions) using a combination of SMS and postal approaches. Data collected included demographics, COVID infection and shielding status, physical (MSK-HQ) and mental health (PHQ8 and GAD7) and global impact on physical or mental health (4 options: none-severe). Ethical approval was obtained (REC Ref 21/PR/0867). Results: 639 people completed the survey, of whom 287 (44.9%) completed online. Mean (sd) age was 64.5 (13.1) years and 384 (64.7%) were female. The majority of people had RA although 57 (9%) reported more than one inflammatory condition. 349 (57.9%) of people were advised to shield. Rates of COVID infection were relatively low across the groups (Table 1 ). 254 (41.2%) reported moderate or severe impact of the pandemic on physical health, which impacted least in people with RA. 244 (39.4%) reported moderate or severe impact of the pandemic on mental health with 175 (28.7%) reporting moderate depression (PHQ8 ≥ >10) and 138 (22.6%) moderate anxiety (GAD-7≥10). Conclusion: Reported COVID infections were low in our cohort. The pandemic had significant effects on physical and mental health, which appeared less in people with RA than other inflammatory conditions. Disclosure: S. Hider: None. S. Muller: None. L. Gray: None. F. Manning: None. M. Brooks: None. D. Heining: None. A. Menon: None. J. Packham: None. S. Raghuvanshi: None. E. Roddy: None. S. Ryan: None. I. Scott: None. Z. Paskins: None.